THE IMPLEMENTATION OF TOTAL PHYSICAL RESPONSE (TPR) METHOD TO TEACH VOCABULARY IN E-LEARNING - Dewi, Noviya Lakshita; Fatmawati, Ayu (Jurnal Pendidikan Bahasa Inggris Proficiency, 2022)
This research was starting from the researchers' case about learning vocabulary for young learners who have to face the digital era, especially in the Pandemic era Covid 19. The researcher investigated one of suitable method for teaching vocabulary to young learners, which is called TPR. For this reason, the researcher wants to see the teaching of vocabulary to young learner using TPR. This research is a qualitative descriptive research. The subjects of this research are the owner of English Box Course, a vocabulary tutor and learners. Data collection in this research was carried out in three ways, namely: observation, interviews, and documentation and using three instruments there are observation checklist, interview guide, and list of documentation. Data analysis was carried out according to theory Miles and Hubermen, namely: data reduction, data display, and verification. The results of this research is explained into three parts: 1) The implementation of Total Physical Response (TPR) method in the term of planning, process and evaluation of teaching vocabulary through E-Learning: a) There are two steps in the planning, those are make a lesson plan and media preparation. b) The process of implementation of Total Physical Response (TPR) method to teach vocabulary in E-Learning is started with apperception. c) The evaluation is taken in general of learning-teaching process that aims to make sure understanding of the students. 2) The implementation of Total Physical Response (TPR) method in teaching vocabulary through E -Learning produce exciting and enjoyable response of two students. 3) It is conducted oral and movement assessment test of the implementation of Total Physical Response (TPR) method in teaching vocabulary through E-Learning.